Glycoproteins IIb and IIIa and Platelet Thrombospondin in a Liposome Model of Platelet Aggregation - Rybak, M E (Thrombosis and Haemostasis, 1986)
Platelet membrane glycoproteins IIb and IIIa and platelet thrombospondin were incorporated onto phosphatidylcholine liposomes, by freeze thawing and sonication. Protein orientation on the liposomes was confirmed by susceptibility to neuraminidase cleavage and binding to lentil lectin-Sepharose (GPIIb-IIIa liposomes) and to heparin-Sepharose (thrombospondin liposomes). Glycoproteins Ilb-IIIa bound 125I-fibrinogen with Kd of 7.5 × 10™7M. Binding was reversible and calcium-dependent. Ilb-IIIa liposomes underwent fibrinogen-dependent aggregation in the presence of 10 mM CaCl2. Maximal aggregate formation was observed with a combination of IIb-IIIa liposomes and thrombospondin liposomes. This aggregation was partially inhibited by preincubation with monoclonal antibodies to the IIb-IIIa complex. Addition of EDTA caused complete reversal of aggregates. Thrombospondin liposomes also underwent fibrinogen and calcium dependent aggregation, however, this aggregation was less than that observed with the GPIIb-IIIa liposomes. Maximal aggregate formation was observed with a mixture of IIb-IIIa liposomes and thrombospondin liposomes. These studies demonstrate that GPIIb-IIIa and thrombospondin can be incorporated into phospholipid vesicles with preservation of function. Direct evidence is provided to demonstrate that glycoprotein lib and Ilia and fibrinogen are sufficient for platelet aggregation and to demonstrate that thrombospondin may also contribute to platelet aggregation.
Keywords: Platelet; Thrombospondin; Glycoproteins